PENCATATAN ILMU DALAM PERSPEKTIF HADIS - Ahmadi, Ahmadi; Fattah, Mohammad; Amalia, Riadlatul (Program Studi Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2023)
Books as one of the educational tools that need to support the educational process are important. Because it contains various knowledge that will be transformed to students. Also, including Islamic students. This article will discuss the importance of recording knowledge in the perspective of the hadith of the Prophet Muhammad. This research uses a literature study approach. The primary data sources in this study were the book Shaḥīḥ Al-Bukhāri by Muhammad bin Ismail bin Ibrahim bin Al-Mughirah bin Barduzbah Al-Ju'fi Al-Bukhori and the book Fatḥul Bārī bi Syarḥi Shaḥīḥ al-Bukhāri by Al-Hafizh Ibnu Hajar Al- Asqalani. While secondary data sources in this study are books, journals and other documents related to the discussion in this study. From the results of the research found in Shaḥīḥ al-Bukhāri, there are at least four hadiths relating to the recording of knowledge, namely in hadith numbers 111, 112, 113 and 114. It is also obligatory to record legal knowledge since the time of the Prophet Muhammad SAW. even though a person has a strong memory, it will decrease with age. Recording of knowledge: writing, note-taking and literacy, is one of the important things, so that it can be known or learned by the next generation